"Mind the gap" acute coronary syndrome in women: A contemporary review of current clinical evidence. (15th January 2017) - Davis, Elizabeth; Gorog, Diana A.; Rihal, Charanjit; Prasad, Abhiram; Srinivasan, Manivannan
Abstract: The incidence and prevalence of coronary artery disease in women has exceeded that in men over the past four decades, and although a significant decline in mortality has occurred in the past two decades, there is a growing body of evidence suggesting that there are gender differences between the clinical manifestations and course of coronary artery disease, as well as differences in treatment and treatment response. This review article considers the current literature regarding the gender-specific manifestation of acute coronary syndromes. Through the review of basic science articles, subsets of trial data, and meta-analyses, the gender-specific differences in within acute coronary syndromes are considered in terms of diagnostic dilemmas, pathophysiology, and treatment options (including pharmacological, percutaneous and surgical methods). Finally, acute coronary syndromes and their management in the special circumstance of pregnancy are also reviewed. Highlights: Coronary artery disease is the leading cause of death in older women. Studies suggest women tend to have a worse prognosis compared to men. Conventional coronary risk factors alone are unlikely to represent the full picture. Treating women of child-bearing age with ACS presents specific challenges. Our understanding of ACS in women (as distinct from ACS in men) continues to evolve.